Preparation of ciprofloxacin-coated zinc oxide nanoparticles and their antibacterial effects against clinical isolates of Staphylococcus aureus and Escherichia coli - Sepideh, Seif; Zahra Bahri, Kazempour; Mohammad Reza, Pourmand; Hamid Reza, Shahverdi; Massoud, Amanlou; Roya, Bazl; Zeynab Esmail, Nazari; Ahmad Reza, Shahverdi (Arzneimittelforschung, 2011)
In the present research study, ciprofloxacincoated zinc oxide nanoparticles were prepared using a precipitation method. The nature of interactions between zinc oxide nanoparticles and ciprofloxacin (CAS 85721-33-1) was studied by Fourier transform infrared spectroscopy. The results show that the carbonyl group in ciprofloxacin is actively involved in forming chemical – rather than physical – bonds with zinc oxide nanoparticles. Also the antibacterial activity of free zinc oxide nanoparticles and ciprofloxacin-coated zinc oxide nanoparticles have been evaluated against different clinical isolates of Staphylococcus aureus and Escherichia coli. The free zinc oxide nanoparticles did not show potent antibacterial activity against all test strains. In contrast, only the low concentrations of ciprofloxacincoated zinc oxide nanoparticles (equivalent to the sub-minimum inhibitory concentrations of pure ciprofloxacin) considerably enhanced the antibacterial activity of zinc oxide nanoparticles against different isolates of Staphylococcus aureus and Escherichia coli (4 to 32 fold increase). The result is of particular value, since it demonstrates that, by using biocompatible zinc oxide nanoparticles in combination therapy, lower amounts of antibiotics may be needed.
Keywords: Antibacterials; CAS 85721-33-1; Ciprofloxacin; Escherichia coli; Staphylococcus aureus; Zinc oxide nanoparticles